Thanksgiving [videorecording (DVD)] - Roth, Eli, 1972-; Rendell, Jeff; Dempsey, Patrick, 1966-; Verlaque, Nell; Rae, Addison; Brooks, Jalen Thomas; Manheim, Milo, 2001-; Hoffman, Rick, 1970-; Gershon, Gina (Sony Pictures Home Entertainment, 2024)
After a Black Friday riot ends in tragedy, a mysterious Thanksgiving-inspired killer terrorizes Plymouth, Massachusetts, the birthplace of the infamous holiday.